Terapi Psikoreligius Menggunakan Terapi Al-Qur’an terhadap Halusinasi Pasien Skizofrenia - Susanti, Icih; Suryani, Suryani; Rafiyah, Imas (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine psycho-religious therapy by reading and listening to the Koran for hallucinations in schizophrenia patients. The method used is a literature study using PubMed, CINAHL, and Google Scholar with inclusion criteria for quantitative research articles focusing on Al-Qur'an therapy, publications in 2018-2022, and full text available in Indonesian and English. The results of the study showed that there were seven articles analyzed that showed their effectiveness in reducing hallucinations in schizophrenic patients using Al-Quran therapy by reading, listening, and SQEFT activities. This therapy is applied to conditions of stress, anxiety, depression, and other psychological disorders. The implementation procedure is to read Surah Al-Fatihah and listen to Surah Al-Baqarah for 30 minutes. In conclusion, Al-Qur'an therapy has proven to be effective in reducing hallucinations in schizophrenia patients. Keywords: Al-Qur'an, Hallucinations, Schizophrenia, Psychoreligious Therapy